Green synthesis of silver nanoparticles. Complementary techniques for characterization - S.D. Khizhnyak; A.I. Ivanova; V.M. Volkova; E.V. Barabanova; P.M. Pakhomov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2023)
The work presents the results of green synthesis (biosynthesis) of silver nanoparticles using aqueous extracts of maple and oak leaves. The efficiency of the synthesis, size and shape of the formed nanoparticles were studied using UV-visible spectroscopy, dynamic light scattering, atomic force microscopy and scanning electron microscopy techniques. It was found that the formation of silver nanoparticles is accompanied by the appearance of a plasmon resonance band in the electronic spectra of aqueous extracts, the maximum of which depends on the concentration of silver nitrate and is in the range of ~420-429 nm in the spectra of maple leaves, and in the spectra of oak extracts there is a shift towards longer wavelengths ~425-435 nm, which correspond to the formation of nanoparticles of larger size. According to the dynamic light scattering data, the size of nanoparticles in the maple extracts is of about 60-68 nm and in the oak samples of ~107 nm. The differences in the size and shape of nanoparticles obtained in the maple and oak phytoextracts detected by atomic force microscopy and scanning electron microscopy are explained by the different composition of bioactive substances in the plants involved in the reduction of silver ions and stabilization or modification of the surface of silver nanoparticles.